EFFECTIVENESS OF A SELF-INSTRUCTIONAL MODULE ON KNOWLEDGE REGARDING REHABILITATION AMONG PATIENTS WITH ILEAL CONDUIT AT AIMS, KOCHI - ANSU MARY MATHEW; SHEELA PAVITHRAN (International Journal of Pharma and Bio Sciences, 2016)
Ileal conduit is the most common surgical procedure performed for individuals after surgical removal of the bladder for severe trauma or malignancy, a congenital defect of the urinary tract, and neurogenic nonfunctioning bladder in which other methods to maintain urinary flow are unsatisfactory. This urinary diversion being permanent, knowledge and skill in the self care and rehabilitation is very important. The present one group pretest-posttest study on “Effectiveness of a self-instructional module on knowledge regarding rehabilitation among patients with ileal conduit” conducted through telephonic interview among 30 patients selected by purposive sampling showed a statistically significant improvement in knowledge regarding rehabilitation (t(29)=16.279, p<0.05). Problems with personal relationship (76.7%), body image disturbance (76.7%), constipation (63.3%), foul smelling urine (26.7%) and infection (20%) were the major problems faced by the patients with ileal conduit. The study report that the self–instructional module is an effective means to improve the knowledge and useful as subjects could read and clear theirdoubt at their own pace.